Analisis Struktur Jaringan Sosial sebagai Indikator Polarisasi dan Fragmentasi Politik Digital: Telaah Kasus [CONSOLIDATED] Singapore General Election 2025 Thread di Forum HardwareZone - Vyco, Parlin FVB Berek; Yuliandri, Putrawan (FISIP UPNVJ, 2025)
This study analyzes the evolution of structural polarization within digital discussion networks surrounding the 2025 Singapore General Election (SGE) on the HardwareZone forum, integrating the framework of Interian et al. (2023) with the temporal approach of Alamsyah et al. (2021). Employing a longitudinal descriptive-quantitative design, the research uses Social Network Analysis (SNA) to trace changes in the structure of social interactions across five electoral phases: pre-election, parliamentary dissolution, campaign period, polling day, and post-election. The unit of analysis is the interactional ties among forum users, based on 17,263 valid relations extracted from 33,571 posts, collected via web scraping using Python (BeautifulSoup) and processed with NetworkX. Four metrics are used to measure polarization: Modularity (Q), Homophily (H), the E–I Index, and Betweenness Centrality (BC). The results show that polarization intensifies during the campaign phase (Q: 0.47→0.62; H: 0.58→0.71; E–I: –0.23→–0.46) and declines in the post-election period as high-BC bridging actors emerge to restore network connectivity. The findings underscore that digital polarization is dynamic, fluctuating with electoral momentum, and demonstrate the effectiveness of integrating Python–NetworkX-based SNA with temporal analysis in the study of online political polarization.